SECONDARY TRIGEMINAL NEURALGIA FROM ACOUSTIC NEUROMA : A CASE REPORT - Pinzon, Rizaldy Taslim; Maharani, Regina Vika (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
There are varying reports of 6 to 16% of patients with symptoms similar to trigeminal neuralgia having intracranial tumors. Acoustic neuromas are benign cerebellopontine angle (CPA) tumors that are most frequently responsible for TN-like symptoms. It has been claimed that magnetic resonance imaging can detect brain tumors with great accuracy (92% to 93%). We describe a case of an adult male patient who had trigeminal neuralgia and temporomandibular dysfunction, which were cured; nonetheless, an acoustic neuroma in the CPA was later discovered.